(untitled) (MAUSAM, 1978)
Two troughs of low pressure are generally noticed over Indian region during the monsoon. One is the monsoon trough Over Gangetic plain persisting throughout the monsoon season. The other is of comparatively less pronounced trough persisting off the west coast of India, being most prominent during the month of July. Vortices embedded in these troughs cause considerable amount of rainfall. While the vortices and low pressure areas associated with the monsoon trough passing over Gangetic plain have been studied extensively, those embedded in the trough off the west coast do not appear to have received enough attention. In this paper the study of latter vortices during the month of July has been conducted. The following conclusions have been arrived at. These vortices are most prominent in the month of July. They have a tendency to form in series in first half of the month of July, (b) They form just south of Goa, (c) They move generally northwards with an approximate speed of 100 km per day. During second half of the month of July some of them are found to move northwestwards, (d) Heavy rainfall associated with them has the peculiarity that coastal stations get more rain than the Ghats, and (e) There may be an association between the formation of the series of vortices, during first half of July and the existence of an upper air cyclonic circulation between 2.1 and 3.6 km above sea level over Gujarat region and neighbourhood.